Wire feeding type aluminum alloy laser cladding method based on pre-laid reinforced particles
By laying TiC particle powder on the surface of the aluminum alloy and combining swing laser and push-pull wire feeding technology, the problem of poor coating bonding in aluminum alloy laser cladding is solved, and the wear resistance and coating quality of the aluminum alloy surface are significantly improved.
Patent Information
- Application Number
- CN202411192335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-28
AI Technical Summary
During the laser cladding process, aluminum alloys have low absorption and poor bonding of the oxide film and the matrix, resulting in poor coating quality, especially insufficient bonding and wear resistance.
The wire feeding aluminum alloy laser cladding method is adopted to uniformly lay TiC particle powder on the surface of the aluminum alloy, and the oxide film is broken by shaking laser, and the wire feeding is controlled by push-pull wire feeding to ensure the consistency of the coating and stability, improve the diffusion and metallurgical bond of ceramic particles in the melt pool.
It significantly improves the wear resistance and coating bonding of the aluminum alloy surface, forms a high-performance cladding coating, and solves the problem of difficulty in laser cladding.
Smart Images

Figure CN119287358A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser processing, and in particular relates to a wire-feeding aluminum alloy laser cladding method based on pre-laid reinforced particles. Background Art
[0002] Aluminum and aluminum alloys are the top non-ferrous metals and the preferred materials for lightweighting. As their annual output is second only to steel, they have become one of the most widely used materials. Aluminum alloys have many advantages, such as good plasticity and toughness, high specific strength, low density, easy processing, and low thermal expansion coefficient. They are widely used in the fields of automobiles, ships, aerospace, etc. Especially in the development of the new era, in order to reduce the weight of the car and reduce fuel consumption, the amount of aluminum alloy is continuously increased in the structural parts of the car, so as to achieve energy conservation and emission reduction of the car. During use, aluminum alloy parts are subject to external impact, scratches and corrosion, which often cause local wear, thus leading to failure of the overall parts. Surface modification technology can effectively solve this problem. It can greatly improve the hardness, wear resistance, heat resistance and other excellent properties of the surface of the strengthened material. At present, the commonly used surface modification technologies at home and abroad mainly include thermal spraying technology (flame spraying, plasma spraying, flame spraying), vapor deposition technology (CVD, PVD), coating technology (electroplating, anodizing, chemical plating), high-energy beam (laser, electron beam, ion beam) surface modification technology, among which thermal spraying technology, vapor deposition technology and coating technology are relatively traditional surface modification technologies, and there are certain defects. For example, the thermal spraying technology has poor coating adhesion, the coating technology has great environmental pollution, and the coating produced by the vapor deposition technology is very thin. These defects make it difficult to apply these traditional surface strengthening technologies to the manufacture of aluminum alloy wear-resistant parts.
[0003] Laser cladding technology is a type of high-energy beam surface modification technology. It has many advantages, such as high energy utilization, low pollution, metallurgical bonding between the coating and the substrate, and uniform coating structure. It is a promising green manufacturing technology and has been widely used in surface modification of steel materials. However, since aluminum alloys have special physical properties different from those of ferrous metals, it is difficult to laser clad high-performance coatings on their surfaces, and the quality of the cladding layer is poor, especially the poor bonding between the cladding layer and the substrate and the easy generation of cracks in the cladding layer.
[0004] There are two problems with the existing technology. First, it is difficult to prepare high-performance laser cladding coatings. Due to the low laser absorption rate of aluminum alloy, most of the laser energy is reflected by the surface of the aluminum alloy during the laser cladding process, which is not conducive to the formation of a molten pool. Due to the strong electronegativity of aluminum alloy, it is easy to react with other metal elements on the bonding interface to form intermetallic compounds. Metallic compounds generally have high hardness, but are relatively brittle. They are prone to cracks under the action of thermal stress, resulting in a decrease in the quality of the cladding layer. Second, the cladding coating has poor bonding. There will be an oxide film on the surface of the aluminum alloy. The melting point of the oxide film is as high as 2054°C. The cladding temperature sometimes does not reach its melting point. At this time, the unmelted solid aluminum oxide film will hinder the metallurgical bonding between the molten cladding layer alloy and the aluminum alloy substrate, resulting in poor bonding between the cladding layer and the substrate. The melting point of the aluminum alloy itself is low, and it is easy to cause a high dilution rate after high-energy laser irradiation, which damages the performance of the substrate material. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a wire-feeding aluminum alloy laser cladding method based on pre-laid reinforced particles.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a wire-feeding aluminum alloy laser cladding method based on pre-laid reinforced particles, comprising:
[0009] The TiC particle powder is evenly spread on the aluminum alloy surface substrate;
[0010] The aluminum alloy substrate with the powder spread on it is fixed on the platform, and the laser cladding processing parameters are set;
[0011] Move the laser to the starting point of a single laser cladding process, use a swinging laser to break the oxide film on the surface of the aluminum alloy, and promote the diffusion of ceramic particles in the molten pool. At the same time, push-pull wire feeding is used to control the feeding speed and position of the wire. The wire is smoothly fed into the molten pool during the cladding process to ensure the consistency and stability of the coating during the cladding process. Under the action of the laser, the wire and the reinforcing particles melt to form a molten pool.
[0012] Then it cools and solidifies to complete the single-pass laser cladding forming;
[0013] The laser power is 1400W-1800W, the laser swing speed is set to 200-550mm / s, the shielding gas parameter is set to 15L / min, the defocus amount is +5mm, the scanning speed is set to 6mm / s, and the wire feeding speed is 10mm / s.
[0014] The TIC powder spreading thickness is 0.1 to 0.3 mm.
[0015] As a preferred solution of the method of the present invention, the particle size of the TiC particle powder is 15 μm to 53 μm.
[0016] As a preferred embodiment of the method of the present invention, the TIC powder is spread to a thickness of 0.2 mm.
[0017] As a preferred solution of the method of the present invention, the wire material comprises solid aluminum alloy wire material, and the aluminum alloy wire material comprises ER5356 with a diameter of 1.6 mm.
[0018] As a preferred solution of the method of the present invention, the laser power is 1400-1600W.
[0019] As a preferred solution of the method of the present invention, wherein: the laser power is 1600W.
[0020] As a preferred embodiment of the method of the present invention, the protective gas includes Ar gas.
[0021] As a preferred solution of the method of the present invention, the laser swing speed is set to 400-550 mm / s.
[0022] As a preferred solution of the method of the present invention, the laser swing speed is set to 300-550 mm / s.
[0023] As a preferred solution of the method of the present invention, the laser swing speed is set to 480 mm / s.
[0024] Beneficial effects of the present invention:
[0025] (1) The present invention ensures the consistency and stability of the coating during the cladding process by adopting push-pull wire feeding, reduces the generation of bubbles, uses a swinging laser to promote the diffusion of ceramic particles in the molten pool, and the nonlinear superposition effect of the physical properties of the ceramic reinforcement phase and the aluminum alloy matrix phase, organically combines the good toughness and machinability of the aluminum alloy matrix with the high hardness and high wear resistance of the ceramic reinforcement phase, the cladding coating has high performance, the ceramic particles are evenly distributed, and the wear resistance of the aluminum alloy surface is significantly improved;
[0026] (2) The present invention utilizes the high laser absorption rate of TIC powder and spreads the TIC powder on the aluminum alloy substrate to reduce the aluminum alloy's reflectivity to the laser. At the same time, the use of a swinging laser also helps to break up the oxide film on the surface of the aluminum alloy, thereby reducing the generation of defects. The ceramic particles are partially dissolved in the molten pool, which enhances the metallurgical bonding between the cladding coating and the substrate and improves the bonding of the cladding coating. Finally, a cladding coating with good bonding is obtained, thereby solving the problem of the difficulty of laser cladding of high-performance coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0028] Figure 1 It is a schematic diagram of an experiment in an embodiment of the present invention;
[0029] Figure 2 A schematic diagram of a swaying laser trajectory in an embodiment of the present invention;
[0030] Figure 3 A schematic diagram of a metallographic image in an embodiment of the present invention;
[0031] Figure 4 Schematic diagram of coating hardness in an embodiment of the present invention;
[0032] Figure 5 Schematic diagram of coating wear in an embodiment of the present invention;
[0033] Figure 6 Schematic diagram of the SEM image of friction and wear in the embodiment of the present invention. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] Working principle of the present invention:
[0038] The method for laser cladding of aluminum alloy based on enhanced particle powder spreading and wire feeding of the present invention first places a rectangular mold on the surface of an aluminum alloy substrate, adds TiC particle powder and scrapes it to make it evenly spread, then removes the mold to achieve preliminary laying of enhanced particles, then uses a clamp to fix the aluminum alloy substrate with the spread powder on a special metal platform, sets the laser parameters of the laser cladding machine including laser power, swing speed, shielding gas parameters, defocusing amount, scanning speed, wire feeding speed, etc. and the moving speed of the robot, determines the starting point and end point of a single channel of additive manufacturing, and compiles a program;
[0039] Then, move the laser to the starting point of a single pass, and control the wire feeding speed and position by push-pull wire feeding to ensure that the wire is smoothly fed into the molten pool. Under the action of the laser, the wire and the reinforcing particles melt to form a molten pool and cool and solidify to complete the single-pass forming. At this point, the entire workflow ends.
[0040] The cross-sectional hardness of the coating in the embodiment of the present invention is tested using a Vickers hardness tester:
[0041] The microhardness of the cladding layer was measured using a HV-1000 Vickers hardness tester. The surface of the test sample was ground flat using a metallographic grinder and polished on a polisher. The load on the hardness tester was 500g and the holding time was 15s. During the test, it was necessary to avoid hard TiC ceramic particles to ensure that the indentation was fully applied to the composite matrix. The indentation was a regular rhombus. A site was selected for testing every 0.1mm. The same site was measured three times and the average value was taken as the final measurement value.
[0042] The friction and wear properties of the samples were tested using a UMT-3 testing machine. The composite materials were subjected to friction and wear in a ball-disc reciprocating mode, and GCr15 was used as the grinding ball material. The sample surfaces were ground and polished to ensure that all sample surfaces maintained the same roughness. The mass of the samples before wear was tested, and the load of the friction and wear testing machine was set to 3N, the friction rate to 10mm / s, and the test time to 60min. After the test was completed, the mass of the sample after the test was measured to obtain the wear mass of the sample.
[0043] A schematic diagram of the method of the present invention is shown in Figure 1 , specifically:
[0044] (1) Place a rectangular mold on the surface of a 6061-T6 aluminum alloy substrate, add TiC particle powder, use a scraper to scrape off excess powder, so that the TiC particle powder is evenly spread on the aluminum alloy surface substrate, and remove the mold.
[0045] (2) Use a clamp to fix the aluminum alloy substrate with powder spread on a special metal platform, and set the laser parameters of the laser cladding machine. The laser power is 1400W, 1600W and 1800W respectively, the laser swing speed is set to 480mm / s, the shielding gas parameter is set to 15L / min, the defocus amount is +5, the scanning speed is set to 6mm / s, the wire feeding speed is 10mm / s, and the wire material is ER5356 solid wire.
[0046] (3) Set the robot movement speed, determine the starting and ending points of a single pass in the additive manufacturing process, compile the robot program, move the laser head to the vicinity of the starting point of a single pass of laser cladding, start the robot program, move the laser to the starting point of a single pass of laser cladding, and the wire feeder feeds the wire. The robot drives the laser to move in a straight line from the set starting point to the end point. Under the action of the laser, the wire and the reinforcing particles melt to form a molten pool, which is then cooled and solidified. The TIC residual particles are evenly distributed in the aluminum alloy cladding coating, completing the single pass forming of the laser cladding process.
[0047] Example 1
[0048] A method for laser cladding of aluminum alloy based on enhanced particle powder laying and wire feeding, comprising the following steps:
[0049] (1) placing a rectangular mold on the surface of an aluminum alloy substrate, adding TiC particle powder, scraping off excess powder with a scraper, so that the TiC particle powder is evenly spread on the aluminum alloy surface substrate, and then removing the mold, wherein the particle size of the added TiC particle powder is 15 μm to 53 μm, and the TIC powder spreading thickness is 0.2 mm;
[0050] (2) Use a fixture to fix the aluminum alloy substrate with powder spread on a dedicated metal platform, first set the laser parameters of the laser cladding machine, then set the movement speed of the robot, determine the starting and ending points of a single pass of the additive manufacturing process, compile the robot program, move the laser head to the vicinity of the starting point of a single pass of laser cladding, and start the robot program;
[0051] Among them, the laser parameters of the laser cladding machine are: laser power is set to 1600W, laser swing speed is set to 480mm / s, shielding gas parameter is set to 15L / min, defocus is set to +5mm, scanning speed is set to 6mm / s, and wire feeding speed is set to 10mm / s;
[0052] See the schematic diagram of the swing laser trajectory for Figure 2 .
[0053] (3) Move the laser to the starting point of a single laser cladding process, and use push-pull wire feeding to control the feeding speed and position of the wire to ensure that the wire is smoothly fed into the molten pool during the cladding process, ensuring the consistency and stability of the coating during the cladding process. The wire feeder feeds the wire, and the robot drives the laser to move in a straight line from the set starting point to the end point. Under the action of the laser, the wire and the reinforcing particles melt to form a molten pool, which is then cooled and solidified to complete the single-pass forming of the laser cladding process. Among them, the wire of the laser cladding machine uses solid aluminum alloy wire.
[0054] (4) After the experiment, a part of the cross section was cut to prepare a metallographic sample, and a metallographic microscope was used to observe the coating forming quality and whether the internal reinforcement particle distribution was uniform;
[0055] The aluminum alloy substrate and TiC particles are metallurgically bonded to form a fusion layer, and then the hardness of the coating cross section is tested. The hardness of the coating and the aluminum alloy substrate in this experiment are tested respectively, and then the wear resistance of the aluminum alloy surface is tested, and the surface is observed using a SEM electron microscope.
[0056] Example 2
[0057] Under the conditions of Example 1, the laser parameters for controlling the laser cladding machine are different, and the other conditions are the same as those of Example 1, specifically as follows:
[0058] Laser parameters of the laser cladding machine: laser power was set to 1400 W, laser swing speed was set to 480 mm / s, shielding gas parameter was set to 15 L / min, defocus was set to +5 mm, scanning speed was set to 6 mm / s, and wire feeding speed was set to 10 mm / s.
[0059] Example 3
[0060] Under the conditions of Example 1, the laser parameters for controlling the laser cladding machine are different, and the other conditions are the same as those of Example 1, specifically as follows:
[0061] Laser parameters of the laser cladding machine: laser power was set to 1800 W, laser swing speed was set to 480 mm / s, shielding gas parameter was set to 15 L / min, defocus was set to +5 mm, scanning speed was set to 6 mm / s, and wire feeding speed was set to 10 mm / s.
[0062] Please provide the test results of the coating performance of Examples 1 to 3.
[0063] Table 1
[0064] Example 1 Example 2 Example 3 hardness 141.5HV 130.4HV 134.7HV Wear 0.55mg 0.73mg 0.67mg
[0065] See the picture of cladding coating observed under optical microscope. Figure 3,It can be seen that the cross section of the cladding layer was ground and polished, and observed using an optical microscope. It can be seen that the bottom of the cladding layer formed a good metallurgical bond with the substrate, and residual TIC particles were distributed. Since TIC particles are light, most of them floated above the molten pool during laser cladding.
[0066] Sample hardness picture The hardness of the substrate and coating is measured using a Vickers hardness tester. Figure 4 It can be concluded that the hardness of the cladding layer is higher than that of the substrate, and the hardness of the cladding layer is the highest when 1600W; the schematic diagram of the comparison of the wear amount of the cladding layer and the substrate is shown in Figure 5 , it can be seen that the wear amount of the sample at 1600W is the smallest, but whether it is 1400W or 1800W, the wear amount is much less than that of the substrate;
[0067] After the friction and wear test, the surface morphology of the sample was observed under the electron microscope: The surface of the sample after the wear test was observed by scanning with an electron microscope. Figure 6 ,It can be seen that the relative surface wear scars of the sample at 1600W are shallower and the wear degree is lower, but whether it is 1400W or 1800W, the wear degree is lower than that of the substrate.
[0068] Comparative Example 1
[0069] A layer prepared by a laser cladding forming method for an aluminum alloy plate surface provided in the patent document entitled "A laser cladding forming method for an aluminum alloy plate surface" with application publication number CN114381727A;
[0070] The B4C particles are placed separately in the powder feeder, the aluminum alloy welding wire is fixed on the automatic wire feeder, and the powder feeding nozzle is combined with the MIG welding gun. The height of the welding gun and the angle of the powder feeding nozzle are adjusted to feed the wire and powder. The coupling point falls on the aluminum alloy substrate. High-purity argon with a purity of 99.99% is used as the shielding gas and powder feeding gas. The aluminum alloy MIG welding parameters and injection powder feeding parameters are adjusted. When the MIG welding is started on the surface of the aluminum alloy plate, the side injection powder feeding is turned on to inject the B4C particles into the aluminum alloy molten pool. The MIG welding current is 60-100A single pulse DC, the voltage is 15-20V, the shielding gas flow rate is 12-15L / min, the B4C powder feeding speed is 1-2g / min, and the powder feeding gas flow rate is 2 ~3L / min, cladding speed 300~400mm / min, B4C particle reinforced Al-based composite cladding layer consists of aluminum alloy matrix and B4C reinforced particles, and utilizes extremely inert gas shielded welding-MIG welding to transition aluminum alloy welding wire to the surface of aluminum alloy plate while assisting the side injection of B4C particles to melt into the Al-based cladding layer, that is, to prepare B4C particle reinforced Al-based composite cladding layer on the surface of aluminum alloy plate, the B4C particle coverage rate of the surface layer is 30%~40%, and the content gradually decreases from the surface along the depth direction, the thickness of the aluminum alloy plate surface laser cladding forming method is 2~3mm, the B4C particle size is 120 mesh, and the aluminum alloy wire material used for the Al matrix of the cladding layer is ER5356 welding wire with a diameter of 1.2mm.
[0071] At the same time, through experimental comparison between the comparative example and the embodiment, it is found that in the comparative example, since the reinforcing particles in the coating are fed by a powder feeder, on the one hand, the complexity of the equipment is increased, thereby increasing the manufacturing cost, and on the other hand, since the powder is very easy to splash during the cladding process, resulting in a low powder material rate, the method adopted by the present invention has a higher material utilization rate, and does not require an external synchronous powder feeder for powder feeding, so the processing cost is also lower;
[0072] In summary, the aluminum-based composite coating processed by the present invention has the characteristics of high quality, high efficiency, energy saving and consumption reduction, and meets the requirements of green manufacturing development.
[0073] Comparative Example 2
[0074] Under the conditions of Example 1, the laser is not swung, that is, the laser swing speed is set to 0 mm / s, and the other conditions are the same as those of Example 1.
[0075] Comparative Example 3
[0076] Under the conditions of Example 1, the laser swing speed is set to 200 mm / s, and the other conditions are the same as Example 1.
[0077] Comparative Example 4
[0078] Under the conditions of Example 1, the laser swing speed is set to 300 mm / s, and the other conditions are the same as Example 1.
[0079] Comparative Example 5
[0080] Under the conditions of Example 1, the laser swing speed is set to 550 mm / s, and the other conditions are the same as Example 1.
[0081] See Table 2 for the test results of the coating properties of Example 1 and Comparative Examples 2 to 5.
[0082] Table 2
[0083] Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 hardness 141.5HV 119.4HV 127.1HV 135.7HV 137.6HV Wear 0.55mg 1.03mg 0.75mg 0.63mg 0.61mg
[0084] As can be seen from Table 2, the laser swing speed has a significant effect on the microhardness and wear resistance of the cladding layer. When the laser swing speed is set to 0mm / s, the laser energy is too concentrated, resulting in poor quality of the cladding layer, the lowest microhardness, the largest wear, and the lowest wear resistance among all samples. When the laser swing speed is set to 200mm / s and 300mm / s, the laser energy distribution is relatively uneven, and the microhardness and wear resistance of the coating are lower than those of the cladding coating when the laser swing speed is set to 480mm / s. When the laser swing speed is set to 550mm / s, although the microhardness and wear resistance of the coating are improved compared with those when the laser swing speed is set to 0mm / s, 200mm / s and 300mm / s, due to the excessively fast laser swing speed and the excessive dispersion of the laser energy, its microhardness and wear resistance are still lower than those of the cladding coating when the laser swing speed is set to 480mm / s.
[0085] At the same time, when TiC particle powder is not spread and directly clad, since aluminum alloy is a highly reflective material, higher laser energy is required, and the bonding performance between the cladding coating and the aluminum alloy substrate is poor; when laser cladding is performed by feeding TIC powder, since TIC powder is lighter, it is easy to splash during powder feeding, and the powder feeding process is complicated and the cost is higher.
[0086] The present invention ensures the consistency and stability of the coating during the cladding process by adopting push-pull wire feeding, reduces the generation of bubbles, uses a swinging laser to promote the diffusion of ceramic particles in the molten pool, and the nonlinear superposition effect of the physical properties of the ceramic reinforcement phase and the aluminum alloy matrix phase, organically combines the good toughness and machinability of the aluminum alloy matrix with the high hardness and high wear resistance of the ceramic reinforcement phase, the cladding coating has high performance, the ceramic particles are evenly distributed, and the wear resistance of the aluminum alloy surface is significantly improved;
[0087] The present invention utilizes the high laser absorption rate of TIC powder and spreads the TIC powder on the aluminum alloy substrate to reduce the reflectivity of the aluminum alloy to the laser. At the same time, the use of the swinging laser also helps to break the oxide film on the surface of the aluminum alloy, reducing the generation of defects. The ceramic particles are partially dissolved in the molten pool to enhance the metallurgical bonding between the cladding coating and the substrate, improve the bonding of the cladding coating, and finally obtain a cladding coating with good bonding, thereby solving the problem of the difficulty of laser cladding high-performance coatings.
[0088] In summary, the present invention proposes for the first time an aluminum alloy cladding method in which TIC powder is spread on an aluminum alloy substrate and combined with a swinging laser + push-pull wire feeding, which effectively reduces the reflectivity during aluminum alloy laser cladding and prepares a high-performance aluminum alloy cladding coating, and has good application prospects.
[0089] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A wire-feeding aluminum alloy laser cladding method based on pre-laid reinforced particles, characterized in that: include, The TiC particle powder is evenly spread on the aluminum alloy surface substrate; The aluminum alloy substrate with the powder spread on it is fixed on the platform, and the laser cladding processing parameters are set; Move the laser to the starting point of a single laser cladding process, use a swinging laser to break the oxide film on the surface of the aluminum alloy, and promote the diffusion of ceramic particles in the molten pool. At the same time, push-pull wire feeding is used to control the feeding speed and position of the wire. The wire is smoothly fed into the molten pool during the cladding process to ensure the consistency and stability of the coating during the cladding process. Under the action of the laser, the wire and the reinforcing particles melt to form a molten pool. Then it cools and solidifies to complete the single-pass laser cladding forming; The laser power is 1400W-1800W, the laser swing speed is set to 200-550mm / s, the shielding gas parameter is set to 15L / min, the defocus amount is +5mm, the scanning speed is set to 6mm / s, and the wire feeding speed is 10mm / s. The TIC powder spreading thickness is 0.1 to 0.3 mm.
2. The method according to claim 1, characterized in that: The particle size of the TiC particle powder is 15 μm to 53 μm.
3. The method according to claim 1 or 2, characterized in that: The TIC powder spreading thickness is 0.2 mm.
4. The method according to claim 1 or 2, characterized in that: The wire material includes solid aluminum alloy wire material, and the aluminum alloy wire material includes ER5356 and has a diameter of 1.6 mm.
5. The method according to claim 1, characterized in that: The laser power is 1400-1600W.
6. The method according to claim 5, characterized in that: The laser power is 1600W.
7. The method according to claim 1, characterized in that: The protective gas includes Ar gas.
8. The method according to claim 1, characterized in that: The laser swing speed is set to 300-550 mm / s.
9. The method according to claim 8, characterized in that: The laser swing speed is set to 400-550 mm / s.
10. The method according to claim 9, characterized in that: The laser swing speed is set to 480 mm / s.
Citation Information
Patent Citations
Aluminum alloy plate surface laser cladding forming method
CN114381727A
Laser melting deposition ceramic particle enhanced metal-base composite coating based on tubular powder core wire and machining method
CN110965060A
Multi-wire synchronous additive manufacturing method for laser-induced arc oscillation
CN113751877A
Babbitt metal laser cladding processing method and laser cladding piece
CN114875402A
Preparation method of ceramic reinforced aluminum matrix composite wear-resistant coating, aluminum alloy material and train brake disc
CN116180071A
Cited By
Laser cladding method for sealing surface of valve seat
CN120006286A
Aluminum-based composite material manufacturing device and method based on wire powder composite laser additive material
CN121972812A
Aluminum matrix composite manufacturing apparatus and method based on wire powder composite laser additive
CN121972812B